A vigilance decrement comes along with an executive control decrement: Testing the resource-control theory - Luna, Fernando Gabriel (2022)
A decrease in vigilance over time is often observed when performing prolonged tasks, a phenomenon known as “vigilance decrement.” The present study aimed at testing some of the critical predictions of the resource-control theory about the vigilance decrement. Specifically, the theory predicts that the vigilance decrement is mainly due to a drop in executive control, which fails to keep attentional resources on the external task, thus devoting a larger number of resources to mind-wandering across time-on-task. Datasets gathered from a large sample size (N = 617) who completed the Attentional Networks Test for Interactions and Vigilance—executive and arousal components in Luna, Roca, Martín-Arévalo, and Lupiáñez (2021b, Behavior Research Methods, 53[3], 1124–1147) were reanalyzed to test whether executive control decreases across time in a vigilance task and whether the vigilance decrement comes along with the decrement in executive control. Vigilance was examined as two dissociated components: executive vigilance, as the ability to detect infrequent critical signals, and arousal vigilance, as the maintenance of a fast reaction to stimuli. The executive control decrement was evidenced by a linear increase in the interference effect for mean reaction time, errors, and the inverse efficiency score. Critically, interindividual differences showed that the decrease in the executive—but not in the arousal—component of vigilance was modulated by the change in executive control across time-on-task, thus supporting the predictions of the resource-control theory. Nevertheless, given the small effect sizes observed in our large sample size, the present outcomes suggest further consideration of the role of executive control in resource-control theory.